2006
DOI: 10.1007/s10826-006-9033-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Dieting and Nondieting Adolescents in a Psychiatric Inpatient Setting

Abstract: The clinical and psychosocial characteristics of 239 dieting and nondieting adolescents (61% female; mean age = 15.3) recruited from an inpatient psychiatric setting were examined. Dieting adolescents were compared to nondieting adolescents on exercise frequency, weight control behaviors, risky behaviors, psychiatric comorbidity and distress, eating disorder symptomatology, smoking, coping, and family factors. While dieters did not statistically differ from nondieters on scores of body mass index, dieting yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Despite the severity of these associated psychosocial problems, ED psychopathology has received less attention in psychiatrically hospitalized adolescents (5). Perhaps of particular importance for clinicians working with adolescent psychiatric inpatient populations is the growing body of research documenting an association between ED psychopathology and suicidality across diverse clinical and community samples.…”
mentioning
confidence: 99%
“…Despite the severity of these associated psychosocial problems, ED psychopathology has received less attention in psychiatrically hospitalized adolescents (5). Perhaps of particular importance for clinicians working with adolescent psychiatric inpatient populations is the growing body of research documenting an association between ED psychopathology and suicidality across diverse clinical and community samples.…”
mentioning
confidence: 99%
“…Other studies also have yielded similar results suggesting that eating- and weight-related disturbances increase risk for subsequent depression [ 25 , 26 ]. Adding further complexity, a study conducted by Abrantes and colleagues [ 27 ] found that dieters at an adolescent inpatient psychiatric program were more likely to meet criteria for an ED, reported greater levels of distress, and had higher rates of major depression in the previous year compared to non-dieters.…”
Section: Reviewmentioning
confidence: 99%
“…For example, given the high comorbidity between smoking and psychiatric disorders (Lasser et al, 2000) and well-documented beneficial effects of exercise on well-being (Penedo & Dahn, 2005) and depressive symptoms (Carek, Laibstain, & Carek, 2011), smokers with psychiatric disorders might especially benefit from exercise-based interventions. However, elevated rates of eating disorders, weight concerns, and body image dissatisfaction, as well as smoking for weight control, are observed in adolescent females receiving psychiatric treatment (e.g., Abrantes, Strong, Ramsey, Lewinsohn, & Brown, 2006). Therefore, these females may be especially motivated by extrinsic reasons (i.e., weight control) to exercise and to use smoking and exercise jointly for weight control.…”
Section: Introductionmentioning
confidence: 99%